2016
DOI: 10.32890/mjli2016.13.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Anxiety in English Conversation Classrooms Among Thai Students

Abstract: Purpose-This paper reports on a part of a larger research project concerning the conceptualisation of English language speaking-inclass anxiety, attitudes to speaking English in class and self-ratings of English-speaking ability, and perceived sources of this situationspecific anxiety. Methodology-The participants in this study were 282 Thai university students of English as a foreign language (EFL) studying English Conversation courses at a university in Thailand. Levels of anxiety (on average and by dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 12 publications
11
63
1
3
Order By: Relevance
“…The overall findings indicated that the participants are extremely worried about making linguistic mistakes and lacking linguistic knowledge including grammar, vocabulary, and pronunciation. This result is in line with most of the previous studies " (Akkakoson,[2]; Ahmed, [1]; Diaab, [7]; Han et al…”
Section: ) Communication Apprehensionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall findings indicated that the participants are extremely worried about making linguistic mistakes and lacking linguistic knowledge including grammar, vocabulary, and pronunciation. This result is in line with most of the previous studies " (Akkakoson,[2]; Ahmed, [1]; Diaab, [7]; Han et al…”
Section: ) Communication Apprehensionsupporting
confidence: 92%
“…The items were 1, 2, 4, 5,6,7,8,9,10,12,15,18,19,21,22,23,29,30, and 33. Of these seven items linked to communicative apprehension; (1, 4, 9, 18, 22, 29, and 33) three items for fear of negative evaluation; (2,15,19), two items associated with competitiveness; (7,23), three were off for oral test anxiety; (8, 10 and 21), and four items associated with others causes of speaking anxiety (5,6,12,30). This was done by arranging all grade nine students alphabetically and taking every 15 th item in the population after a random starts with an item from 1 to 15.…”
Section: Sample Size and Sampling Techniquesmentioning
confidence: 99%
“…In considering the issue of anxiety in speaking classrooms, many English language teachers and researchers in the EFL countries focus on the attempt to alleviate the issue by revealing the contributing factors of anxiety and the way to deal with the issue. Among the other causes of anxiety experienced by the students in speaking classrooms, the most salient factors include fear of negative evaluation/making mistakes (see Aeni et al 2017;Akkakoson, 2016;Anandari, 2015;Ariyanti, 2016;Juhana, 2012;Liu & Jackson, 2008;Noprival, 2016), lack of motivation and confidence (see Ariyanti, 2016;Juhana, 2012;Marwan, 2008;Meylina, 2017;Sutarsyah, 2017), limited linguistic competence (see Aeni et al 2017;Akkakoson, 2016;Noprival, 2016;Aulia, V, 2018), and limited language practice (Coskun, 2016;Marwan, 2008). Although these studies have listed the possible causes of speaking anxiety, these studies have not put a great emphasis on the interrelationship between each cause.…”
Section: The Causes Of Speaking Anxietymentioning
confidence: 99%
“…Furthermore, many researchers also outline that communication apprehension is caused by limited extensive background knowledge and vocabulary of the learning topics being discussed which lead them to feel anxious and unable to perform speaking skills (Aeni et al, 2017;see also Prieto Castillo, 2007;Mukminin et al, 2015;Noprival, 2016). Additionally, other studies have also discovered that limited speaking opportunities in the classroom can also provoke the students' speaking anxiety due to the high emphasis on grammar and vocabulary memorization (Akkakoson, 2016; see also Coskun, 2016).…”
Section: Linguistic-related Causesmentioning
confidence: 99%
See 1 more Smart Citation